Acoustic quality and health in urban environments (SALVE) – a pilot study in the metropolitan Ruhr region, Germany. Issue 1 (4th May 2021) - Sutcliffe, Robynne; Lawrence, Bryce T.; Ahmed, Salman; Gruehn, Dietwald; Moebus, Susanne
ABSTRACT: Acoustic quality has long been a concern in the disciplines of architecture, building technology, and construction engineering. In health research, acoustic quality has been understood as a health risk factor of noise and, thus, limited to reducing sound decibel levels. Noise mitigation measures exclusively aim to reduce noise levels below a threshold. In contrast, acoustic environments are a composition of all acoustic events of the natural and physical setting, typically determined by sound level, frequency, time, and space. Thus, soundscape ecology provides a suitable methodical approach to analyze associations between acoustic quality, the built environment, and human health. This paper debates how SALVE, a two-year interdisciplinary pilot study, may fill the knowledge gap and contribute to sound and health research. SALVE aims to identify criteria for human health-promoting acoustic environments. By making annual direct and automated auditory measurements of a robust land-use sample, a large multi-seasonal urban sound dataset will be established. This data is merged with health data from the population-based Heinz Nixdorf Recall study and will form a starting point for an innovative approach to better understand the impacts of acoustic quality on urban public health beyond noise protection.